Detection of abnormal urine findings among asymptomatic pre-clinical medical students in Universiti Malaysia Sarawak - Than, T. A.; Dayangku Norlida, A.O; Zulkarnaen, M.; Ahadon, M.; Billy, A. L.; Haidah, S. M.; Zul, F. H.; Adlina, M. N. (2021)
Introduction: Renal disease may be an incidental finding during urinalysis. A dipstick urinalysis was conducted to estimate the prevalence of abnormal urine findings among asymptomatic pre-clinical medical students in the Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak. Materials & Methods: A cross sectional study involving 286 students was carried out from November 2018 to August 2019. First morning midstream urine samples were obtained from students and were tested by dipstick method. Students with abnormal urine findings were retested after 15 days. Results: Thirty-three (11.5%) students had urinary abnormalities at the first screening; 54.5% of them still had abnormal results at the second screening. Ketonuria was the most common abnormality found with a prevalence of 2.4%, followed by glycosuria (1.4%), leucocyturia (1.4%), haematuria (0.7%) and nitriuria (0.3%). In microscopic examination, leukocyturia was the most common abnormality detected in four students (1.4%) followed by isolated haematuria in two of them. Among students with leucocyturia, two were diagnosed to be due to urinary tract infection. There was statistically significant association between glycosuria and males. The prevalence of ketonuria was higher in females; however, no significant difference was observed between male and female students. Proteinuria was not present in any participant. Discussion: Urinary abnormalities were detected among asymptomatic preclinical medical students on dipstick and microscopic analyses. Further investigations are needed to elucidate the underlying aetiology of these abnormal findings.